Method for preparing silylated ionic copolyurethane having improved elasticity

JP2023071609A5Inactive Publication Date: 2025-11-06BOSTIK SA(FR)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022176112
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-11-04
Filing Date
2022-11-02
Publication Date
2025-11-06
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing silylated polyurethanes, particularly SPURs, face challenges with elongation at break being insufficient for industrial applications, require toxic tin-based catalysts, and exhibit color changes with organic catalysts, necessitating a solution that enhances elasticity and eliminates the need for these catalysts.

Method used

A process for preparing ionic silylated copolyurethanes with ureido-alkylene-alkoxysilane end groups, using specific polyisocyanates, polyols, and amines, which are crosslinked without catalysts, resulting in compositions that form adhesive seals with high elongation at break and improved mechanical properties.

Benefits of technology

The solution achieves adhesive seals with elongation at break exceeding 100%, up to 200%, and tensile breaking stress of at least 3 MPa, meeting industrial requirements without the use of toxic catalysts and maintaining robustness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2023071609000001
    Figure 2023071609000001
  • Figure 2023071609000002
    Figure 2023071609000002
  • Figure 2023071609000003
    Figure 2023071609000003
Patent Text Reader

Abstract

To provide a method for preparing a composition of silylated ionic copolyurethane that has improved elastic property, especially higher elongation at break, and to provide a composition of silylated ionic copolyurethane obtainable by said method.SOLUTION: Provided is a method, which is a method for preparing ionic silylated copolyurethane containing two ureido-alkylene-alkoxysilane end groups, and includes (i) carrying out a polyaddition reaction between a polyisocyanate, a carboxylic acid diol and a polyol composition comprising a polyol having Mn of 2500 g / mol or more and a polyol having Mn of less than 2500 g / mol to form a composition of a copolyurethane having -NCO end group, (ii) neutralizing the product formed with a tertiary amine, (iii) reacting with aminosilane derived from secondary amine.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for preparing a silylated ionic copolyurethane composition having improved elastic properties, particularly higher elongation at the breaking point. The subject of the present invention is also a silylated ionic copolyurethane composition that can be obtained by the method described above. Finally, the present invention relates to an adhesive and / or sealant crosslinkable composition comprising the copolyurethane composition, and to a method for assembling two substrates using the composition. [Background technology]

[0002] Silylated polyurethanes, in combination with mineral fillers, are included in the most popular sealant compositions on the market. These compositions have the advantage of not containing isocyanates, particularly monomeric diisocyanates. Therefore, these compositions constitute a preferred alternative from a toxicological standpoint to compositions based on polyurethanes having isocyanate-terminated groups.

[0003] The aforementioned silylated polyurethane generally has terminal groups, which are alkoxysilane reactive groups that react with moisture in the air or from the assembled substrate when the sealant is used, and is therefore often described as "pre-polyurethane".

[0004] Therefore, this reaction, called crosslinking, occurs in the presence of moisture through the hydrolysis of alkoxysilane groups in the prepolymer, followed by their condensation to form siloxane bonds (-Si-O-Si-), which then link the prepolymer chains to form a three-dimensional polymer network.

[0005] Therefore, the completion of this crosslinking reaction after a period called the "crosslinking time" has the effect of integrating the substrates to be assembled and forming a three-dimensional network with the desired mechanical properties within the adhesive seal.

[0006] Among these properties, the adhesive seal thus formed must exhibit great robustness, indicated by its high resistance to deformation. It must also exhibit flexibility (or elasticity) that allows it to adapt to the relative motion of the substrates it joins, for example, under the influence of dimensional changes induced by temperature changes, or under the influence of mechanical stresses that the assembly may otherwise experience during its lifespan.

[0007] The deformation resistance of a sealant is often quantified in practice by its fracture stress (expressed in Pa). The latter is simply defined as the stress that must be applied to a test specimen made of the sealant in a tensile test to achieve failure.

[0008] The elasticity of the sealant portion is generally expressed by the measured elongation at break (expressed as a percentage), which is defined as the elongation measured for the test specimen at the moment of fracture in the tensile test described above.

[0009] The most well-known silylated polyurethanes are generally prepared by a two-step process.

[0010] The first step involves forming a polyurethane having isocyanate-terminated groups by carrying out a polyaddition reaction between a polyetherdiol (particularly poly(propylene glycol)) and a polyisocyanate (preferably diisocyanate).

[0011] The second step involves reacting the pre-polyurethane thus obtained with an aminosilane containing at least one alkoxysilane group to obtain a polyurethane main chain containing two alkoxysilane terminal groups, each linked to the chain by a urea functional group.

[0012] The silylated polyurethane obtained through this two-step process will be referred to as "SPUR" below.

[0013] However, the crosslinking times of these silylated polyurethanes, particularly those of these SPURs, need to be accelerated to meet the needs of the user, and for this purpose, it is essential to incorporate a crosslinking catalyst into these silylated polyurethanes, particularly the sealant compositions containing these SPURs.

[0014] Generally, the crosslinking catalysts contained in silylated polymers, particularly sealant or adhesive compositions based on SPURs, are metal catalysts, more specifically tin-based catalysts such as dibutyltin dilaurate (DBTDL), dibutyltin diacetate or dibutyltin bis(acetylacetonate) or dioctyltin bis(acetylacetonate). However, these catalysts are the subject of criticism regarding their toxicity or environmental impact, and particularly when these metal catalysts remain in the adhesive seal after the composition has been crosslinked, their use is restricted or even avoided by the manufacturers concerned.

[0015] Organic crosslinking catalysts derived from nitrogen-containing heterocycles such as 1,8-diazabicyclo[5.4.0]undec-7-ene (also called DBU) or 1,5,7-triazabicyclo[4.4.0]dec-5-ene (also called TBD) are used as alternatives to metal catalysts, particularly tin-based catalysts. However, they have the drawback of causing a color change, generally to yellow, in the adhesive seal, which is due to their migration to the surface of the seal.

[0016] Ionic silylated copolyurethanes containing two ureido-alkylene-alkoxysilane end groups are known from WO 2021 / 079063 pamphlet.

[0017] Such copolyurethanes are prepared by a method derived from the method for producing SPUR recalled above, the first step being to modify poly(propylene glycol) to form a copolyurethane having isocyanate-terminated groups by reacting it with a diisocyanate, which is a carboxylic acid diol. Then, the pendant carboxylic acid groups of the thus obtained copolyurethane are neutralized with an amine, and then an aminosilane is used as in the second step of the method for producing SPUR.

[0018] The copolyurethanes taught by this PCT application advantageously result in crosslinkable sealant and / or adhesive compositions with reduced crosslinking times compared to prior art SPURs, particularly in the absence of catalysts, especially tin-based catalysts. Furthermore, adhesive seals formed by crosslinking of the adhesive and / or sealant crosslinkable composition comprising the copolyurethane and at least one mineral filler in the presence of moisture also have better mechanical properties, in particular improved resistance to deformation and improved elasticity, indicated by increased fracture stress and elongation at fracture, respectively.

[0019] However, this fracture elongation generally does not exceed 100%, which may prove insufficient in terms of the expected performance results of sealants in certain industrial fields, such as construction or the bonding of automotive windshields in the automotive industry.

[0020] In fact, in modern architectural technology, sealants are widely used to join (or assemble or bond) the most diverse substrates, such as steel or concrete substrates, or other porous materials with uneven surfaces that are permeable and brittle. These sealants must provide appropriate elastic properties to flexibly follow the movement of the adhesive seal caused by the relative movement of the substrates to which they are applied, under the influence of various external factors such as external temperature or ground movement. [Overview of the project]

[0021] Therefore, an object of the present invention is to provide an ionic silylated copolyurethane, whose crosslinking, in combination with mineral fillers in a sealant composition, has the effect of forming an adhesive seal exhibiting a better elongation at break, particularly an elongation at break of 100% or more, while maintaining other characteristics at an acceptable level.

[0022] Another object of the present invention is to overcome the drawbacks of silylated polyurethanes known in the prior art, particularly the drawbacks of SPUR.

[0023] Another object of the present invention is to propose silylated polyurethanes that do not require, or substantially do not require, a tin-based catalyst or an organocatalyst derived from a nitrogen-containing heterocycle for crosslinking.

[0024] Another object of the present invention is to propose a silylated polyurethane that can be crosslinked in the absence of a catalyst.

[0025] Another object of the present invention is to propose a sealant composition based on silylated polyurethane that enables a reduction in crosslinking time without or substantially without the addition of a catalyst.

[0026] Another object of the present invention is to propose a silylated polyurethane-based sealant composition that produces an adhesive seal having improved fracture stress properties, particularly a fracture stress of at least 3 MPa.

[0027] These objectives can be achieved, in whole or in part, by compositions of silylated copolyurethanes having alkoxysilane-terminated groups, and methods for their preparation are described below. [Modes for carrying out the invention]

[0028] Preparation method: The subject of the present invention is, firstly, a method for preparing a composition of an ionic silylated copolyurethane comprising two ureido-alkylene-alkoxysilane terminal groups, wherein the method is • Polyisocyanate of formula (iA) (A): OCN-R 1 -NCO(iA) (In the formula, R 1 This represents a divalent hydrocarbon group containing 5 to 45 carbon atoms, which may be aromatic or aliphatic, linear, branched or cyclic, and may contain at least one heteroatom selected from O, S, and N. • A polyol composition (B) containing the following: - At least one polyol (B1) having a number-average molecular weight (Mn) of 2500 g / mol or more, and - At least one polyol (B2) having a number-average molecular weight (Mn) of less than 2500 g / mol • Carboxylic acid diol (C) of formula (iC): TIFF2023071609000001.tif46170 (in the formula, -R 0 This represents an alkyl group containing a hydrogen atom or 1 to 18 carbon atoms. -x and y may be the same or different integers in the range of 1 to 8. -z is an integer in the range of 0 to 8. (i) A step of forming a copolyurethane composition having a -NCO-terminated group by carrying out a polyaddition reaction between the two, Next Step (ii) involves reacting the copolyurethane composition formed in step (i) with amine (D) of formula (iiD), N(R)(R')(R”)(iiD) (In the formula, -R, R', and R'' may be the same or different, and each represents a saturated, unsaturated, or aromatic hydrocarbon group that optionally contains a heteroatom selected from N, O, and S. -R, R', and R'' further specify that the tertiary amine (D) is a linear, branched, or cyclic amine or polyamine having a number-average molar mass Mn in the range of 59 to 6000 g / mol and a pKa greater than 8), then The composition of the copolyurethane having -NCO terminal groups formed in step (ii) is represented by the formula (iiiE): TIFF2023071609000002.tif34170(wherein -R 3 represents a linear or branched divalent alkylene group containing 1 to 6 carbon atoms, -R 4 represents a linear or branched alkyl group containing 1 to 4 carbon atoms, -R 5 represents a linear or branched alkyl group containing 1 to 4 carbon atoms, an alkylcarbonyl group containing 2 to 8 carbon atoms, or a dialkylimino group containing 3 to 8 carbon atoms, -p is an integer equal to 0, 1 or 2, -R 6 represents a phenyl group, a linear, branched or cyclic alkyl group containing 1 to 6 carbon atoms, or a group selected from the following groups, - formula (IIc): TIFF2023071609000003.tif20170 - formula (IId): TIFF2023071609000004.tif29170 - formula (IIe): TIFF2023071609000005.tif28170 wherein R 7 is a linear or branched alkyl group containing 1 to 6 carbon atoms as follows, formula (IIf): -CH2-COO - ,HN + (R)(R’)(R”)(IIf), and formula (IIg): -CH2-CH2-COO - ,HN + (R)(R’)(R”)(IIg) wherein R, R’ and R” are the groups defined above) with an aminosilane (E) derived from a secondary amine, and step (iii), and is a method that continuously includes them.

[0029] The implementation of the method according to the present invention results in the formation of a novel silylated ionic copolyurethane in the form of a composition, and it is now known that the combination of this composition with a mineral filler yields a crosslinkable sealant and / or adhesive composition having a crosslinking time that is favorably comparable to the crosslinking time of silylated ionic copolyurethanes taught in International Publication No. 2021 / 079063, in the absence of a catalyst. Furthermore, the adhesive seals resulting from the crosslinking of the composition exhibit resistance to deformation quantified by a tensile breaking stress of at least 3 MPa, which corresponds to the expected robustness of adhesive seals in the construction industry or any industrial field of interest. Finally, the adhesive seals have a breaking elongation ranging from over 100%, even over 150%, to close to or exceeding 200%, and are therefore significantly greater than the breaking elongation of silylated ionic copolyurethanes taught in International Publication No. 2021 / 079063.

[0030] In this specification, the average molecular weight Mn is measured by size exclusion chromatography (or SEC), which is also referred to as gel permeation chromatography (or GPC). The calibration performed is typically PEG (polyethylene glycol) or PS (polystyrene), preferably PS.

[0031] Process (i): Polyisocyanate (A): Step (i) uses polyisocyanate (A) of formula (iA). OCN-R 1 -NCO(iA) (In the formula, R 1 (This represents a divalent hydrocarbon group containing 5 to 45 carbon atoms, which may be aromatic or aliphatic, linear, branched or cyclic, and which may contain at least one heteroatom selected from O, S, and N.)

[0032] Preferably, the polyisocyanate (A) of formula (iA) has the group R 1 The following is an example where one of the following divalent groups is selected, and the following formula shows the two free valencies: a) Divalent groups derived from isophorone diisocyanate (IPDI): TIFF2023071609000006.tif30170·b) Divalent groups derived from dicyclohexylmethane 4,4'- and 2,4'-diisocyanates (HMDI): TIFF2023071609000007.tif18170 or TIFF2023071609000008.tif28170·c) Groups derived from toluene 2,4- and 2,6-diisocyanates (TDI): TIFF2023071609000009.tif33170·d) Groups derived from diphenylmethane 4,4'- and 2,4'-diisocyanates (MDI): TIFF2023071609000010.tif23170·e) Groups derived from m-xylylene diisocyanate (m-XDI): TIFF2023071609000011.tif26170·f) Groups derived from hexamethylene diisocyanate (HDI): -(CH2)6- •g) Divalent group derived from hexamethylene diisocyanate (HDI) allophanate of formula (iA'): TIFF2023071609000012.tif57170 (in the formula, -i is an integer in the range of 2 to 5. -j is an integer in the range of 1 to 2. -R 11 This represents a saturated or unsaturated, cyclic or acyclic, linear or branched hydrocarbon group containing 6 to 14 carbon atoms. -R 12 This represents a divalent propylene group, i, j, R 11 and R 12 (This is the case where the hexamethylene diisocyanate allophanate corresponding to formula (iA') contains an isocyanate group NCO content in the range of 12% to 14% by weight relative to the weight of the allophanate.)

[0033] That base R 1Polyisocyanates corresponding to the above groups a) to f) are well known to those skilled in the art and are widely available on the market. 1 The polyisocyanate corresponding to the above-mentioned divalent group g) is sold by Vencorex under the name "Tolonate®," for example, "Tolonate®X FLO 100."

[0034] According to a particularly preferred modification of the method according to the present invention, polyisocyanate (A) is isophorone diisocyanate (IPDI).

[0035] Polyol composition (B): Step (i) is, • At least one polyol (B1) having a number-average molecular weight (Mn) of 2500 g / mol or more, A polyol composition (B) is used, which includes at least one polyol (B2) having a number-average molecular weight (Mn) of less than 2500 g / mol.

[0036] According to one embodiment, the polyol composition (B) comprises the at least one polyol (B1) and the at least one polyol (B2).

[0037] According to one preferred variation, the number-average molecular weight (Mn) of the polyol (B1) is in the range of 2500 g / mol to 20000 g / mol, more preferably in the range of 3000 g / mol to 15000 g / mol, particularly in the range of 3200 g / mol to 9000 g / mol, and even more preferably in the range of 3000 g / mol to 5000 g / mol, particularly in the range of 3200 g / mol to 5000 g / mol.

[0038] According to another preferred modification, the number-average molecular weight Mn of the polyol (B2) is 200 g / mol or more and less than 2500 g / mol, and more preferably in the range of 200 g / mol to 2250 g / mol.

[0039] The polyol competitor (B) is favorably, • 10 mol% to 90 mol% polyol (B1), • 10 mol% to 90 mol% polyol (B2), including (or consisting of), The aforementioned mole percentage is expressed based on the total number of moles of (B1) and (B2) present in composition (B).

[0040] If polyol composition (B) contains (or consists of) several polyols (B1) and / or several polyols (B2), it is understood that the previously indicated mole percentage ranges apply to the total number of moles of polyol (B1) and / or the total number of moles of polyol (B2), respectively.

[0041] Preferably, the polyol composition (B) is advantageously, • 10 mol% to 70 mol% polyol (B1), • 30 mol% to 90 mol% polyol (B2), including (or consisting of), The aforementioned mole percentage is expressed based on the total number of moles of (B1) and (B2) present in composition (B).

[0042] A more preferred variation is that the polyol composition (B) consists of 10 mol% to 35 mol% of polyol (B1) and 65 mol% to 90 mol% of polyol (B2), and more preferably, 15 mol% to 30 mol% of (B1) and 70 mol% to 85 mol% of (B2). It has been found that a silylated ionic copolyurethane composition formed by the method according to the present invention, corresponding to such composition (B), exhibits a break point elongation of more than 200% in adhesive seals after use in sealant and / or adhesive compositions.

[0043] According to one particularly preferred embodiment, the polyol composition (B) is, in addition to the polyol (B1) defined above, • A first polyol (B2-1) having a number-average molecular weight Mn of 1250 g / mol or more and less than 2500 g / mol, preferably 1250 g / mol to 2250 g / mol, and • A second polyol (B2-2) having a number-average molecular weight Mn in the range of 200 g / mol to 1000 g / mol, and more preferably in the range of 500 g / mol to 1000 g / mol. It contains (or consists of) two polyols (B2) selected from each of the following.

[0044] According to the latter embodiment, the polyol composition (B) is then preferably, • 15 mol% to 45 mol% polyol (B1), • 10 mol% to 25 mol% polyol (B2-1), • 30 mol% to 70 mol% polyol (B2-2), including (or consisting of), The aforementioned mole percentage is expressed based on the total number of moles of (B1) and (B2) present in composition (B).

[0045] The polyols contained in composition (B), particularly polyols (B1) and (B2), may have a hydroxyl functional value in the range of 2 to 6, preferably 2 to 4, and more preferably 2 to 3. In the context of the present invention, unless otherwise specified, the hydroxyl functional value of a polyol is the average number of hydroxyl functional values ​​per mole of polyol.

[0046] According to one preferred modification, the polyol has a hydroxyl functional value equal to 2.

[0047] The polyols that can be used in composition (B), particularly polyols (B1) and (B2), can be selected from polyester polyols, polyether polyols, polydiene polyols, polycarbonate polyols, and poly(ether carbonate) polyols. The polyols that can be used can also be selected from aliphatic polyols, aryl aliphatic polyols, and aromatic polyols.

[0048] Among polyester polyols, the following are some examples: • Naturally derived polyester polyols, such as castor oil; • Polyester polyols produced from condensation: -One or more aliphatic (linear, branched, or cyclic) or aromatic polyols, such as ethanediol, propane-1,2-diol, propane-1,3-diol, glycerol, trimethylolpropane, hexane-1,6-diol, hexane-1,2,6-triol, butenediol, cyclohexanedimethanol, sucrose, glucose, sorbitol, glycerol, trimethylolpropane, pentaerythritol, mannitol, triethanolamine, N-methyldiethanolamine, and mixtures thereof. -One or more polycarboxylic acids or their esters or anhydride derivatives, such as 1,6-hexanedioic acid, dodecanedioic acid, azelaic acid, sebacic acid, adipic acid, 1,18-octadecanedioic acid, phthalic acid, succinic acid and mixtures thereof, unsaturated anhydrides, such as maleic acid or phthalic anhydride, or lactones, such as caprolactone.

[0049] The polyester polyols mentioned above can be prepared by conventional methods and are mostly commercially available.

[0050] Among polyester polyols, for example, the following products having a hydroxyl functional value equal to 2 can be cited. • Polycaprolactone with a number-average molecular weight (Mn) of approximately 2000 g / mol and a melting point of approximately 50°C, Tone® 0240 (sold by Union Carbide). Dynacoll® 7381 (sold by Evonik) has a number-average molecular weight of approximately 3500 g / mol (Mn) and a melting point of approximately 65°C. Dynacoll® 7360 (sold by Evonik), which is produced from the condensation of adipic acid and hexanediol, has a number-average molecular weight of approximately 3500 g / mol (Mn) and a melting point of approximately 55°C. Dynacoll® 7330 (sold by Evonik) has a number-average molecular weight of approximately 3500 g / mol (Mn) and a melting point of approximately 85°C. Dynacoll® 7363 (sold by Evonik), which is produced from the condensation of adipic acid and hexanediol, has a number-average molecular weight (Mn) of approximately 5500 g / mol and a melting point of approximately 57°C. • Dynacoll® 7250 (sold by Evonik): A polyester polyol having a viscosity of 180 Pa.s at 23°C, a number-average molecular weight (Mn) equal to 5500 g / mol, and a Tg equal to -50°C. • Kuraray® P-6010 (sold by Kuraray): A polyester polyol having a viscosity of 68 Pa.s at 23°C, a number-average molecular weight equal to 6000 g / mol, and a Tg equal to -64°C. • Kuraray (registered trademark) P-10010 (sold by Kuraray): a polyester polyol having a viscosity of 687 Pa.s at 23°C and a number-average molecular weight equal to 10,000 g / mol; and Realky XTR10140 (sold by Cray Valley) has a number-average molecular weight of around 1000 g / mol.

[0051] The polyether polyols that can be used in composition (B), particularly polyols (B1) and (B2), are preferably selected from polyoxyalkylene polyols in which the linear or branched alkylene portion contains 1 to 4 carbon atoms, preferably 2 to 3 carbon atoms.

[0052] More preferably, the polyether polyols that can be used according to the present invention are selected from polyoxyalkylenediols or polyoxyalkylentriols, and more preferably from polyoxyalkylenediols, wherein the linear or branched alkylene portion contains 1 to 4 carbon atoms, preferably 2 to 3 carbon atoms.

[0053] Examples of polyoxyalkylenediols or triols that can be used in accordance with the present invention include, for example, the following: • Polyoxypropylene diol or triol (also known as polypropylene glycol (PPG) diol or triol), • Polyoxyethylene diol or triol (also called polyethylene glycol (PEG) diol or triol), • Polyoxybutylenediol or triol (also known as polybutylene glycol (PBG) diol or triol), • PPG / PEG / PBG diol or triol copolymer or terpolymer, • Polytetrahydrofuran (PolyTHF) diol or triol, Polytetramethylene glycol (PTMG) having a number-average molecular weight in the range of 200 g / mol to 12000 g / mol. Preferably, the polyether polyol contained in composition (B) is selected from polyoxypropylene diols. The above polyether polyols can be conventionally prepared and are widely commercially available. They can be obtained, for example, by polymerization of the corresponding alkylene oxide in the presence of a catalyst based on a bimetallic / cyanide complex.

[0054] As an example of a polyetherdiol, we can cite polyoxypropylene diol, which is sold by Covestro under the name Acclaim (registered trademark), as shown below. Acclaim (registered trademark) 18200 has a number-average molecular weight of approximately 18700 g / mol. Acclaim (registered trademark) 12200 has a number-average molecular weight of approximately 11335 g / mol. • Acclaim® 8200, which has a number-average molecular weight of approximately 8057 g / mol, and • Acclaim® 4200, which has a number-average molecular weight of approximately 4020 g / mol, or • Polyoxypropylene diol, which has a number-average molecular weight of approximately 2004 g / mol and is sold by Dow under the name Voranol P2000, and Voranol® EP 1900 is a bifunctional PPG with a number-average molecular weight of approximately 4008 g / mol.

[0055] Examples of polyethertriols include the following: • A polyoxypropylene triol with a number-average molecular weight of approximately 3554 g / mol, sold by Dow under the name Voranol® CP3355. • Boranol® CP 755, a trifunctional PPG with a number-average molecular weight of approximately 710 g / mol, or other Acclaim® 6300 is a trifunctional PPG with a number-average molecular weight of approximately 5948 g / mol.

[0056] Examples of polytetramethylene glycol (PTMG) with a hydroxyl functional value equal to 2 include the following: • Mn is around 1000 g / mol, Terathane (registered trademark) 1000, Terathane® 650, which has a manganese content of around 650 g / mol, and Terathane® 250 has a manganese content of around 250 g / mol.

[0057] The polydiene polyols that can be used in composition (B), particularly polyols (B1) and (B2), are selected from polybutadienes containing optionally hydrogenated or epoxidized hydroxyl-terminated groups. Preferably, the polybutadiene is selected from optionally hydrogenated or epoxidized butadiene homopolymers and copolymers containing hydroxyl-terminated groups.

[0058] The above hydrogenated derivatives can be obtained by the complete or partial hydrogenation of the double bond of a polydiene containing a hydroxyl-terminated group, and are therefore saturated or unsaturated.

[0059] The above epoxidized derivatives can be obtained by chemoselective epoxidation of the double bond in the main chain of a polydiene containing a hydroxyl-terminated group, and thus contain at least one epoxy group in their main chain.

[0060] Examples of polybutadiene polyols include saturated or unsaturated butadiene homopolymers containing hydroxyl-terminated groups that may be epoxidized, such as those sold by Cray Valley under the names Poly bd® or Krasol®.

[0061] Examples of polycarbonate diols that can be mentioned include the following: • Convergent polyols 212-10 and 212-20, sold by Novomer, having number-average molecular weights (Mn) equal to 1000 and 2000 g / mol, respectively. • Desmophen® C XP 2716, sold by Covestro, has a number-average molecular weight (Mn) equal to 326 g / mol. Polyols C-590, C1090, C-2090, and C-3090, sold by Kuraray, have a number-average molecular weight (Mn) in the range of 500 to 3000 g / mol.

[0062] The polyols that can be used in composition (B), particularly polyols (B1) and (B2), can be further selected from the following bio-based diols. Krasol® F3000, a polyfarnesenediol with a manganese content equal to 3000 g / mol, is sold by Cray Valley. Pripol® 2033, sold by Croda, has a manganese content equal to 970 g / mol.

[0063] According to one preferred modification of the method according to the present invention, the polyols contained in composition (B), particularly polyols (B1) and (B2), are polyetherdiols.

[0064] Carbohydrate diol (C): Step (i) uses the carboxylic acid diol (C) of formula (iC), TIFF2023071609000013.tif46170In the formula, ·R 0 This represents an alkyl group containing a hydrogen atom or 1 to 18 carbon atoms. x and y may be the same or different, and are integers in the range of 1 to 8, • z is an integer in the range of 0 to 8.

[0065] According to an advantageous modification of the method according to the present invention, step (i) uses a carboxylic acid diol (C) of formula (iC), where, ·R 0 This represents an alkyl group containing 1 to 4 carbon atoms, preferably a methyl, ethyl, or n-propyl group, and more preferably a methyl group. x and y are identical, equal to 1, and / or z is equal to 0.

[0066] Specific examples of carboxylic acid diols (C) include the following α,α-dimethylolalkanoic acids. • 2,2-di(hydroxymethyl)propionic acid (or DMPA), • 2,2-di(hydroxymethyl)butyrate, 2,2-di(hydroxymethyl)pentanoic acid.

[0067] According to the most particularly preferred embodiment, the carboxylic acid diol (C) used in step (i) is of the formula: This is 2,2-di(hydroxymethyl)propionic acid, also known as α,α-dimethylolpropionic acid (for convenience, abbreviated as DMPA) from TIFF2023071609000014.tif29170.

[0068] The carboxylic acid diol (C) of formula (iC) is prepared according to conventional organic synthesis processes, for example, as described in U.S. Patent No. 3,412,054, for Union Carbide, and many of them, such as DMPA, are commercially available.

[0069] In step (i) of the method according to the present invention, a polyisocyanate (A), a polyol composition (B), and a carboxylic acid diol (C) are reacted in an amount corresponding to an excess of the number of equivalent -NCO groups of the polyisocyanate (A) relative to the number of equivalent -OH groups provided by composition (B) and diol (C).

[0070] Preferably, these amounts correspond to a -NCO / -OH equivalent ratio between 1.1 and 4.2, preferably between 1.1 and 3.8, and more preferably between 1.1 and 2.

[0071] The ratio is defined as being equal to the number of equivalent -NCO groups of polyisocyanate (A) divided by the sum of the number of equivalent -OH groups provided by polyol composition (B) and carboxylic acid diol (C).

[0072] The amount of reactants added to the reactor by weight is determined by this -NCO / -OH equivalent ratio, and the total hydroxyl value of composition (B) N OH Furthermore, the hydroxyl value N of polyols (B1) and (B2) contained in (or constituting) composition (B) is determined based on the molecular masses of (A) and (C). OHThis is the number of hydroxyl functional groups per gram of polyol, expressed in the form of the equivalent milligrams of KOH used for the quantification of hydroxyl functional groups. The hydroxyl value N of a polyol having a functional value f and a number-average molecular weight Mn is also expressed. OH This can also be estimated from the following formula. N OH =(56.1*f*1000) / Mn In the expression, the sign "*" indicates multiplication.

[0073] The relative amounts of polyol composition (B) and carboxylic acid diol (C) introduced into the reactor for the reaction in step (i) generally correspond to a molar ratio: number of moles of (C) / number of moles of polyols contained in or constituting (B) (more specifically polyols (B1) and (B2)), which can vary within a wide range, possibly from 0.04 to 20, preferably from 0.08 to 0.5, and more preferably from 0.08 to 0.2.

[0074] The polyaddition reaction in step (i) is generally carried out in the presence of a catalyst, which may be any catalyst known to those skilled in the art for catalyzing the formation of polyurethane by the reaction of a polyisocyanate with at least one polyol. Such catalysts are selected, for example, from bismuth and / or zinc carboxylates. A commercially available example is Borchi® KAT 315 from Borchers GmbH, which is bismuth neodecanoate. Alternatively, Borchi® KAT 15 from the same company is zinc neodecanoate.

[0075] Finally, polyaddition reactions generally occur under anhydrous conditions at temperatures between 60°C and 120°C.

[0076] Step (ii): Step (ii) consists of reacting the copolyurethane composition formed in step (i) with amine (D) of formula (iiD): N(R)(R')(R”)(iiD) This corresponds to the neutralization of the pendant-COOH group contained in the main chain of the aforementioned copolyurethane.

[0077] Formula (iiD): ·R, R', and R'' may be the same or different, and each may represent a saturated, unsaturated, or aromatic hydrocarbon group that contains a heteroatom selected from N, O, and S, and R, R', and R'' are further defined as tertiary amines (D) of formula N(R)(R')(R”), where the number-average molar mass Mn is in the range of 59 g / mol to 6000 g / mol and the pKa is greater than 8, and the tertiary amine (D) is a linear, branched, or cyclic amine or polyamine.

[0078] According to one embodiment, the tertiary amine (D) is selected from the following: • Polyethyleneimine, • Polypropyleneimine, • Triethylamine (or TEA, having a pKa equal to 10.75), · 1,8-Diazabicyclo[5.4.0]undeca-7-ene (or DBU), its structural formula is: The filename is TIFF2023071609000015.tif36170, and its pKa is equal to 12; • 1,4-Diazabicyclo[2.2.2]octane (or DABCO), its structural formula is: The filename is TIFF2023071609000016.tif29170, and its pKa is equal to 8.87; · 1,5-Diazabicyclo[4.3.0]nona-5-ene (DBN), its structural formula is: The filename is TIFF2023071609000017.tif36170, and its pKa is equal to 12; • N,N-dicyclohexylmethylamine (or DCHMA), whose pKa is equal to 11; and • Trihexylamine (or THA), with a pKa equal to 10.5.

[0079] A more preferable modification is that the pKa of the corresponding amine is 10 or greater.

[0080] According to the most particularly preferred modification, amine (D) is triethylamine (TEA) or trihexylamine (THA).

[0081] According to another preferred modification, amine (D) is selected from DBU and DABCO. Such amines are often incorporated into sealant and / or adhesive compositions containing SPUR as crosslinking catalysts. In this case, it has the disadvantage of causing yellowing of the adhesive seal after crosslinking of the composition, possibly related to migration to the surface of the seal. In contrast, incorporating such an amine as an agent for neutralizing the pendant carboxylate group in step (ii) of the method according to the present invention has the advantageous effect of not causing yellowing of the adhesive seal resulting from crosslinking of the sealant and / or adhesive composition containing the ionic silylated copolyurethane composition prepared by the method. Such an effect is probably related to the chemical integration of the corresponding quaternary ammonium into the main chain of the copolyurethane.

[0082] The amine (D) is introduced in step (ii) in an amount corresponding to a molar equivalent ratio: [number of moles of (D)] / [number of moles of carboxylic acid diol (C) introduced in step (i)], which is advantageously in the range of 0.5 to 2.5, preferably 0.5 to 2.

[0083] The neutralization reaction is advantageously carried out at a temperature in the range of 20°C to 80°C, preferably 20°C to 40°C.

[0084] Step (iii): Step (iii) is to process the copolyurethane composition having the -NCO-terminated group formed in step (ii) into a compound of formula (iiiE): TIFF2023071609000018.tif30170 (in the formula, ·R 3 This represents a linear or branched divalent alkylene group containing 1 to 6 carbon atoms. ·R 4 This represents a linear or branched alkyl group containing 1 to 4 carbon atoms. ·R 5This represents a linear or branched alkyl group containing 1 to 4 carbon atoms, an alkylcarbonyl group containing 2 to 8 carbon atoms, or a dialkylimino group containing 3 to 8 carbon atoms, and p is an integer equal to 0, 1, or 2. ·R 6 This represents a phenyl group, a linear, branched, or cyclic alkyl group containing 1 to 6 carbon atoms, or a group selected from the following groups: -Formula (IIc): TIFF2023071609000019.tif21170-Formula(IId): TIFF2023071609000020.tif30170-Formula(IIe): TIFF2023071609000021.tif29170, R 7 This is a linear or branched alkyl group containing 1 to 6 carbon atoms; -Formula(IIf): -CH2-COO - , HN + (R)(R')(R")(IIf); and -Equation (IIg): -CH2-CH2-COO - , HN + (R)(R')(R)(IIg) In the formula, R, R', and R'' are groups defined above, and the reaction consists of reacting them with an aminosilane (E) derived from a secondary amine.

[0085] The aminosilane of formula (iiiE) is widely available commercially.

[0086] For example, N-(3-(trimethoxysilyl)propyl)butylamine, available from Evonik under the name Dynasylan® 1189, formula: TIFF2023071609000022.tif18170 can be cited.

[0087] Other aminosilanes of formula (iiiE) can be readily obtained by synthesis from commercially available products. Therefore, this is formula: This is the case of a compound named aminotriethoxysilane DEM+A1100, obtained by reacting diethyl maleate with γ-aminopropyltriethoxysilane, corresponding to TIFF2023071609000023.tif21170. The latter compound is available from Momentive under the name Silquest(registered trademark) A1100, and its formula is: This corresponds to TIFF2023071609000024.tif11170.

[0088] R 6 The aminosilane of formula (iiiE), in which is a group of formula (IIf) or (IIg), can be obtained by neutralizing an amino acid-substituted silylated compound described in U.S. Patent No. 9,567,354 under the name of Shin-Etsu Chemical Co., Ltd. with amine (D) of formula (iiD).

[0089] Preferably, in formula (iiiE) of aminosilane(E), ·R 3 represents a methylene or n-propylene group, preferably an n-propylene group. ·R 4 and R 5 These may be the same or different, and each represents either a methyl group or an ethyl group, preferably a methyl group. p is equal to 0, and / or ·R 6 This is a linear alkyl group containing 1 to 4 carbon atoms, preferably n-butyl, or R 7 R is an alkyl group containing 1 to 3 carbon atoms. 7 This preferentially represents the group of formula (IIc), which is an ethyl group.

[0090] To form a composition of ionic silylated copolyurethane having ureido-alkylene-alkoxysilane terminal groups, the copolyurethane composition having -NCO terminal groups obtained in step (ii) is preferably reacted with substantially stoichiometric amounts of aminosilane (E) according to (iii). The molar amounts of these reactants are preferably 0.90 to 1.1, corresponding to a -NCO / -NH equivalent ratio of about 1.

[0091] During step (iii), the reaction between the -NH group of aminosilane (E) and each of the two -NCO terminal groups of the copolyurethane contained in the composition formed in step (ii) results in the formation of a urea functional group.

[0092] Step (iii) is generally carried out under similar anhydrous conditions at a temperature in the range of 20°C to 80°C, preferably 20°C to 40°C.

[0093] Advantageously, the method according to the present invention is carried out in the absence of water as a solvent. Therefore, the method according to the present invention is carried out without adding any water other than free water, i.e., water that is essentially contained in the components used. In particular, the amount of water introduced into the method according to the present invention is less than 5% by weight, preferably less than 3% by weight, and especially less than 1% by weight, relative to the total weight of the components used.

[0094] According to one preferred modification, the method according to the present invention is carried out in the presence of a plasticizer and / or solvent other than water, which is more preferably introduced in step (i).

[0095] Examples of usable plasticizers include any plasticizer commonly used in the sealant field. The reduced viscosity obtained by using such plasticizers in ionic silylated copolyurethane compositions is advantageous for their handling in industrial facilities.

[0096] Preferably, use the following: • Diisodecyl phthalate, sold by BASF under the name Palatinol (trademark) DIDP. • Alkyl sulfonic acid esters of phenol sold by Lanxess under the name Mesamoll (registered trademark), • Diisononyl 1,2-cyclohexanedicarboxylate, sold by BASF under the name Hexamoll Dinch®. • Pentaerythritol tetravalerate, sold by Perstorp under the trademark name Pevalen (trademark), • Polysiloxane resins, particularly silsesquioxanes having a number-average molecular weight in the range of 400 g / mol to 4000 g / mol, preferably 500 g / mol to 2500 g / mol, such as Dow Corning® 3074 sold by Dow, with a Mn of 1300 to 1500 g / mol.

[0097] Examples of usable solvents include, preferably, aprotic polar solvents selected from ethyl acetate, tetrahydrofuran (or THF), propylene carbonate, N,N-dimethylformamide (or DMF), acetonitrile (or methyl cyanide), or dimethyl sulfoxide (or DMSO).

[0098] Conversely, in this invention, water is not considered a solvent.

[0099] Plasticizers and / or solvents are generally introduced in step (i) in amounts expressed as weight percent in the range of 5% to 20% based on the total weight of the reagents used.

[0100] According to another modification, the method according to the present invention is carried out in the absence of plasticizers and / or solvents.

[0101] According to another preferred modification, which may be combined with the preceding two, a hygroscopic agent (or desiccant) is introduced at the end of step (iii) of the method according to the present invention after the reaction of aminosilane (E) with the copolyurethane composition having the -NCO-terminated group formed in step (ii).

[0102] Suitable desiccants are alkoxysilanes, particularly trialkoxysilanes (especially trimethoxysilane) and alkoxysilanes containing amino, mercapto, or epoxy groups. Examples that may be mentioned include vinyltrimethoxysilane (or VTMO), gamma-glycidyloxypropyltrimethoxysilane, N-beta-(aminoethyl)-gamma-aminopropyltrimethoxysilane, aminopropyltrimethoxysilane, and trimethoxymethylsilane. These compounds are commercially available. For example, vinyltrimethoxysilane is available from Evonik under the trade name Dynasylan® VTMO. Such agents advantageously extend the shelf life of compositions of ionic silylated copolyurethanes formed by the method according to the present invention during storage and transport prior to use.

[0103] The desiccant is generally introduced at the end of step (iii) in an amount expressed as a weight percentage ranging from 0.5% to 5% based on the total weight of the reagents used.

[0104] According to another modification, the method according to the present invention is carried out in the absence of a desiccant.

[0105] Compositions of ionic silylated copolyurethanes: The subject of the present invention is also, secondly, a composition of an ionic silylated copolyurethane comprising two ureido-alkylene-alkoxysilane terminal groups, the composition of which can be obtained by a preparation method according to the present invention.

[0106] The two ureido-alkylene-alkoxysilane terminal groups of the aforementioned copolyurethane are, respectively, of the formula: TIFF2023071609000025.tif28170 and TIFF2023071609000026.tif28170 (in the formula, R 3 , R 4 , R 5 , R 6 And p corresponds to the definitions above.

[0107] Crosslinkable adhesives and / or sealant compositions: The subject of the present invention is, thirdly, a crosslinkable adhesive and / or sealant composition comprising: • At least one composition of an ionic silylated copolyurethane having a ureido-alkylene-alkoxysilane terminal group according to the present invention, and • At least one filler.

[0108] According to one preferred embodiment, the crosslinkable adhesive and / or sealant composition comprises the following: · 10% to 50% (by weight), preferably 20% to 45% (by weight), more preferably 35% to 45% (by weight), of the above copolyurethane composition, and • A filler comprising 20% ​​to 60% (by weight), preferably 30% to 55% (by weight), more preferably 40% to 55% (by weight), These weight percentages are expressed based on the total weight of the composition.

[0109] The fillers that can be used in the compositions according to the present invention can be selected from mineral fillers and mixtures of organic fillers and mineral fillers.

[0110] Examples of mineral fillers that can be used include any mineral filler conventionally used in the field of adhesives and / or sealant compositions. These fillers are in the form of particles of various shapes. They may be, for example, spherical or fibrous, or they may have an irregular shape.

[0111] Preferably, clay, quartz, or carbonate fillers are used.

[0112] More preferably, alkali metal or alkaline earth metal carbonates are used as fillers, and even more preferably, carbonate fillers such as calcium carbonate are used.

[0113] These fillers may be natural or may be treated with, for example, organic acids, such as stearic acid, or a mixture of organic acids mainly consisting of stearic acid.

[0114] Hollow mineral microspheres, such as hollow glass microspheres, or more specifically those made of calcium sodium borosilicate or aluminosilicate, can also be used.

[0115] Examples of organic fillers that can be used include any organic filler, particularly polymer fillers commonly used in the field of adhesives and / or sealant compositions.

[0116] For example, polyvinyl chloride (PVC), polyolefin, rubber, ethylene / vinyl acetate (EVA), or aramid fibers such as Kevlar® can be used.

[0117] Hollow microspheres made from expandable or non-expandable thermoplastic polymers can also be used. In particular, hollow microspheres made from vinylidene chloride / acrylonitrile can be mentioned.

[0118] Preferably, PVC is used.

[0119] The average particle size of the filler that can be used is preferably 10 microns or less, more preferably 3 microns or less, in order to prevent it from settling in the adhesive and / or sealant composition according to the present invention during storage.

[0120] The average particle size is measured for the volume particle size distribution corresponding to 50% (by volume) of the particle sample being analyzed. If the particles are spherical, the average particle size corresponds to the median diameter (D50 or Dv50), which corresponds to the diameter such that 50% of the particles by volume are smaller than the aforementioned diameter. In this application, this value is expressed in micrometers and is determined by laser diffraction in a Malvern-type instrument according to standard NF ISO 13320-1 (1999).

[0121] Advantageously, the compositions according to the present invention do not contain water as a solvent. Therefore, the water content in the compositions according to the present invention is advantageously less than 5% by weight, preferably less than 3% by weight, and particularly less than 1% by weight, relative to the total weight of the composition.

[0122] According to one embodiment, the composition according to the present invention may further include at least a hygroscopic agent, an adhesion promoter, a plasticizer, and / or a rheological agent.

[0123] Suitable desiccants are as described above. Based on the weight of the composition, an amount of desiccant between 0.5% and 5% (by weight) is generally suitable.

[0124] Some of these compounds can also act as adhesion promoters, particularly trialksoxysilanes containing amino, mercapto, or epoxy groups. Examples include: • N-(3-(trimethoxysilyl)propyl)ethylenediamine, sold by Wacker under the name Geniosil® GF9, or other 3-aminopropyltrimethoxysilane, sold by Momentive under the name Silquest A-1110.

[0125] An amount of 0.5% to 2% (based on the weight of the aforementioned composition) would generally be appropriate.

[0126] The usable plasticizers are as described above. Generally, the plasticizer is included in the composition according to the present invention in an amount of 5% to 20% by weight, preferably 10% to 15% by weight, based on the weight of the composition.

[0127] The rheological agents that can be used are any rheological agents conventionally used in the field of adhesives and / or sealant compositions.

[0128] Preferably, one or more rheological agents selected from thixotropic agents, and more preferably selected from the following: PVC plastisols corresponding to suspensions of PVC in a miscible plasticizer, obtained in situ by heating to a temperature in the range of 60°C to 80°C. These plastisols may be those described in particular in the publication Polyurethane Sealants, Robert M. Evans, ISBN 087762-998-6. • Thixotropic polyamides such as Thixatrol® AS8053, available from Elementis. • Humed silica, Urea derivatives obtained from the reaction of aromatic diisocyanate monomers such as 4,4'-MDI with aliphatic amines such as butylamine. The preparation of such urea derivatives is described in particular in French Patent Application Publication No. 1591172.

[0129] The total content of the rheological agent that may be included in the composition according to the present invention can vary from 1% to 40% by weight, preferably 5% to 30% by weight, and more preferably 10% to 25% by weight, based on the weight of the composition.

[0130] The crosslinkable sealant and / or adhesive composition according to the present invention is preferably stored in an anhydrous environment, for example, in sealed packaging that protects the composition from moisture and preferably from light.

[0131] In one preferred embodiment, the crosslinkable sealant and / or adhesive composition has a breaking elongation of more than 100%. In the present invention, the breaking elongation is measured according to standard NF ISO 37 (March 2012) using a "dumbbell" type test specimen measuring 20 mm in length, 4 mm in width, and 3 mm in thickness.

[0132] Preferably, the elongation at the breaking point of the composition is 150% or more, preferably 200% or more.

[0133] Method for preparing crosslinkable sealant and / or adhesive compositions: The present invention also relates to a method for preparing a crosslinkable sealant and / or adhesive composition according to the present invention, the preparation method comprising the step of mixing components that may be present in the composition with a nonionic copolyurethane composition according to the present invention at a temperature generally of 50°C or less, preferably in the range of 5°C to 45°C, and more preferably in the range of 20°C to 30°C.

[0134] In one variation of the process for producing an ionic silylated copolyurethane composition according to the present invention, if the process is carried out in the absence of a plasticizer and / or solvent and / or hygroscopic agent, the plasticizer and / or solvent and / or hygroscopic agent are then advantageously introduced in the components mixed with the copolyurethane composition during the preparation of the sealant and / or adhesive composition. The plasticizer, solvent and hygroscopic agent are as described above.

[0135] Addition and mixing should be carried out under anhydrous conditions.

[0136] Articles containing crosslinkable adhesives and / or sealant compositions: Another subject of the present invention is an article comprising a crosslinkable adhesive and / or sealant composition according to the present invention in airtight packaging protected from air. The airtight packaging is preferably a polyethylene bag or a polyethylene cartridge with a cap.

[0137] Method for assembling two base materials: Finally, the present invention relates to a method for assembling two substrates, The crosslinkable adhesive and / or sealant composition according to the present invention is coated onto at least one of two substrates to be assembled in the form of a layer with a thickness of 0.2 to 5 mm, preferably 1 to 3 mm, at room temperature, and then • To effectively bring the two substrates into contact, This includes methods.

[0138] Suitable substrates include inorganic substrates such as glass, ceramics, concrete, metals or alloys (aluminum, steel, non-ferrous metals, galvanized metals, etc.); or organic substrates such as wood, plastics (as in the automotive sector), PVC, polycarbonate, PMMA, polyethylene, polypropylene, polyester, or epoxy resins; and substrates made of metals and composite materials coated with paints. [Examples]

[0139] The following embodiments are given purely as examples of the present invention and should not be construed to limit its scope.

[0140] Example A (comparative): 1) Preparation of ionic silylated copolyurethane A having a trimethoxysilane-terminated group: Step (i): Synthesis of copolyurethane having isocyanate-terminated groups The following are introduced into a 1-liter reactor equipped with a stirrer, heating means, and thermometer, and connected to a vacuum pump. • 67.34 g of Acclaim® 4200 polypropylene glycol having a hydroxyl value of NOH equivalent to 28 mg KOH / g, corresponding to the number of -OH functionalities equivalent to 33.5 mmol. • 15g of Dow Corning® 3074 silsesquioxane, and • 0.5 g of DMPA (with a molar mass equivalent to 134.13 g / mol) corresponds to the number of -OH functionalities equal to 7.4 mmol.

[0141] The mixture is left under reduced pressure at 110°C for 2 hours to dehydrate it.

[0142] Next, the reactor is cooled to 90°C in order to introduce the following under nitrogen. • 7.87 g of isophorone diisocyanate (IPDI) with a molar mass equal to 222.3 g / mol, i.e., the number of -NCO functionals equal to 70.8 mmol, and • 0.15g of Borchi® KAT 315 catalyst (bismuth neodecanoate).

[0143] The amount of reactant introduced corresponds to a -NCO / -OH molar equivalent ratio equal to 1.73.

[0144] Continue stirring the mixture until it reaches 1.7% by weight of NCO, which is equivalent to 30.6 mmol - corresponding to the number of NCO functionalities.

[0145] Step (ii): Synthesis of ionic copolyurethane having isocyanate-terminated groups Next, at 40°C, 0.38 g of triethylamine (TEA) (equal to a molar mass of 101.19 g / mol), or 3.75 mmol, is introduced into the reaction medium, and the mixture is left to stir for 1 hour.

[0146] Step (iii): Synthesis of ionic silylated copolyurethane Finally, 7.2 g of aminosilane (N-(trimethoxysilyl)propyl)butylamine) (Dynasylan® 1189) with a molar mass equal to 235.4 g / mol, corresponding to a number of -NH-functional groups equal to 30.6 mmol, is added to the reaction medium.

[0147] The molar equivalent ratio of -NCO / -NH- is equal to 1.

[0148] The combined mixture is heated to 40°C and stirred until the reaction is complete, i.e., until the band characteristics of the -NCO functional are no longer detectable by infrared spectroscopy.

[0149] Next, 1 g of vinyltrimethoxysilane (VTMO) is added.

[0150] A mixture consisting of approximately 84 g of ionic silylated copolyurethane, 15 g of Dow Corning® 3074 silsesquioxane, and 1 g of VTMO is obtained in 100 g portions. This mixture is packaged in an aluminum cartridge protected from moisture.

[0151] 2) Preparation of sealant composition A containing ionic silylated copolyurethane A obtained in 1): Sealant A is prepared by simple mixing in a rapid mixer, and the composition of Sealant A is shown below on a weight basis. • 38.11% by weight of the ionic silylated copolyurethane A mixture obtained above, • 45.18% by weight of precipitated calcium carbonate (Calofort SV, available from Specialty Minerals) with an average particle size of less than 1 μm. • 9.6% by weight of ground calcium carbonate with an average particle size of approximately 3 μm (Immerseal 36 S, available from Imerys) • 3.28% thixotropic polyamide (Thixatrol AS8053, available from Elementis) • 2.83% by weight of vinyltrimethoxysilane (VTMO) as a desiccant. • 1% by weight of 3-aminopropyltrimethoxysilane (sold by Momentive under the name Silquest A-1110) as an adhesion promoter.

[0152] The resulting sealant composition is stirred under reduced pressure of 20 mbar for 15 minutes, and then packaged in a polyethylene cartridge to avoid the presence of moisture.

[0153] Next, the composition is subjected to the following tests.

[0154] Measurement of cross-linking time: The cross-linking time is measured by determining the skin-stretching time.

[0155] For this purpose, sealant beads (approximately 10 cm long and 1 cm in diameter) are first deposited onto a cardboard support. Next, using the tip of a low-density polyethylene (LDPE) pipette, the surface of the sealant is touched every minute for up to 2 hours to determine the exact time it takes for the skin to form on the surface. This test is performed under controlled humidity and temperature conditions (23°C and 50% relative humidity).

[0156] The results obtained are expressed in minutes and are shown in Table 2.

[0157] Measurement of fracture stress and elongation at fracture by tensile testing: The measurement principle involves stretching a standard test specimen made of a cross-linked sealant composition in a tensile testing apparatus where a movable jaw moves at a constant speed equal to 100 mm / min, and recording the applied tensile stress (MPa) and elongation (%) of the test specimen at the moment of fracture.

[0158] The standard test specimen is dumbbell-shaped, as specified in the international standard ISO 37. The narrowest part of the dumbbell used has a length of 20 mm, a width of 4 mm, and a thickness of 3 mm.

[0159] To prepare the dumbbells, the composition packaged as described above is extruded into a suitable mold at room temperature and crosslinked for 14 days under standard conditions (23°C and 50% relative humidity).

[0160] This decision was repeated across five dumbbells, and the average results are shown in Table 2.

[0161] Examples 1-5 (according to the present invention): 1) Preparation of compositions of ionic silylated copolyurethanes having trimethoxysilane terminal groups: In step (i), replace Acclaim® 4200 with the amounts of Voranol® EP1900, Voranol® P2000, and Terathane® 650 shown by weight in Table 1, and repeat the method of Example A with the other reagents and components in the amounts also shown in Table 1. 2) Preparation of a sealant composition containing the silylated copolyurethane composition obtained in 1): This sealant is prepared by repeating Example A 2), except that ionic silylated copolyurethane A is replaced with the silylated copolyurethane composition obtained in 1).

[0162] The results are shown in Table 2. Table 1 TIFF2023071609000027.tif193170Table 2 TIFF2023071609000028.tif35170

[0163] Examples 6-9 (according to the present invention): The method for preparing the ionic silylated copolyurethane composition having a trimethoxysilane-terminated group of Example 4 is repeated, but in step (ii), the TEA is replaced with the amine shown in Table 1'. The amounts of reagents and components used are shown in Table 1'.

[0164] The preparation of the sealant in Example A 2) was repeated using the copolyurethane composition obtained in this manner. The results are shown in Table 2'.

[0165] These results tables clearly show that the ionic silylated copolyurethane compositions of Examples 1-9 are entirely advantageous compared to the ionic silylated copolyurethane of Example A, as they enable the creation of silylated sealants that provide a very significant increase in adhesive seals compared to the silylated sealant corresponding to Example A, with fully acceptable breaking strength (around 3 MPa) and elongation at breaking (over 150%) during equivalent crosslinking times. Table 1' TIFF2023071609000029.tif161170Table 2' TIFF2023071609000030.tif35170

Claims

1. 1. A method for preparing a composition of an ionic silylated copolyurethane containing two ureido-alkylene-alkoxysilane end groups, said method comprising: Polyisocyanates (A) of formula (iA): OCN-R 1 -NCO(iA) (In the formula, R 1 represents a divalent hydrocarbon group containing 5 to 45 carbon atoms, which may be aromatic or aliphatic, linear, branched or cyclic, and which may contain at least one heteroatom selected from O, S and N; A composition (B) of polyols comprising: at least one polyol (B1) having a number average molecular weight (Mn) greater than or equal to 2500 g / mol, and at least one polyol (B2) having a number average molecular weight (Mn) of less than 2500 g / mol, and Carboxylic acid diol (C) of formula (iC): (In the formula, -R 0 represents a hydrogen atom or an alkyl group containing 1 to 18 carbon atoms, - x and y may be the same or different and are integers ranging from 1 to 8; -z is an integer ranging from 0 to 8. Step (i) forming a composition of copolyurethane having —NCO end groups by carrying out a polyaddition reaction between Next step (ii) reacting the copolyurethane composition formed in step (i) with an amine (D) of formula (iiD); N(R)(R')(R”)(iiD) (In the formula, -R, R' and R" may be the same or different and each represent a saturated, unsaturated or aromatic hydrocarbon group optionally containing a heteroatom selected from N, O and S; - R, R' and R" are further such that the tertiary amine (D) is a linear, branched or cyclic amine or polyamine having a number average molar mass Mn in the range of 59 to 6000 g / mol and a pKa greater than 8), then The composition of the copolyurethane having —NCO end groups formed in step (ii) is treated with a compound of formula (iiiE): (In the formula, -R 3 represents a linear or branched divalent alkylene group containing 1 to 6 carbon atoms, -R 4 represents a linear or branched alkyl group containing 1 to 4 carbon atoms, -R 5 represents a linear or branched alkyl group containing 1 to 4 carbon atoms, an alkylcarbonyl group containing 2 to 8 carbon atoms, or a dialkylimino group containing 3 to 8 carbon atoms; -p is an integer equal to 0, 1 or 2, -R 6 represents a phenyl group, a linear, branched or cyclic alkyl group containing 1 to 6 carbon atoms, or a group selected from the following groups: -Formula (IIc): Formula (IId): Formula (IIe): In the formula, R 7 is a linear or branched alkyl group containing 1 to 6 carbon atoms as follows: Formula (IIf): -CH 2 -COO - , H.N. + (R)(R')(R")(IIf), and Formula (IIg): -H 2 -H 2 -COOO - ,HN + (R) (R') (R”) (-Ig) and (iii) reacting the resulting compound with an aminosilane (E) derived from a secondary amine of the formula:

2. The group R of the polyisocyanate (A) used in step (i) 1 but, a) a divalent group derived from isophorone diisocyanate (IPDI): b) Divalent groups derived from dicyclohexylmethane 4,4'- and 2,4'-diisocyanate (HMDI): or c) groups derived from toluene 2,4- and 2,6-diisocyanate (TDI): d) groups derived from diphenylmethane 4,4'- and 2,4'-diisocyanate (MDI): e) Groups derived from m-xylylene diisocyanate (m-XDI): f) Groups derived from hexamethylene diisocyanate (HDI): -(CH 2 ) 6 - g) a divalent group derived from a hexamethylene diisocyanate (HDI) allophanate of formula (iA′): (In the formula, -i is an integer ranging from 2 to 5, -j is an integer ranging from 1 to 2, -R 11 represents a saturated or unsaturated, cyclic or acyclic, linear or branched hydrocarbon group containing 6 to 14 carbon atoms, -R 12 represents a divalent propylene group, -i, j, R 11 and R 12 is such that the hexamethylene diisocyanate allophanate corresponding to formula (iA') contains an NCO content of isocyanate groups ranging from 12% to 14% by weight relative to the weight of the allophanate.

3. 2. The method according to claim 1, wherein the polyol (B1) contained in the composition (B) used in step (i) has a number average molecular weight Mn in the range of 2,500 g / mol to 20,000 g / mol, and / or the polyol (B2) contained in the composition (B) used in step (i) has a number average molecular weight Mn in the range of 200 g / mol to 2,250 g / mol.

4. 2. The process according to claim 1, wherein the polyol composition (B) consists of 10 mol % to 35 mol % of polyol (B1) and 65 mol % to 90 mol % of polyol (B2), said molar percentages being expressed based on the total number of moles of (B1) and (B2) present in the composition (B).

5. The polyol composition (B) contains, in addition to the polyol (B1), a first polyol (B2-1) having a number average molecular weight Mn of 1250 g / mol or more and less than 2500 g / mol, preferably 1250 g / mol to 2250 g / mol, and A second polyol (B2-2) having a number average molecular weight (Mn) in the range of 200 g / mol to 1000 g / mol 2. The process according to claim 1, characterized in that it comprises two polyols (B2) selected from the group consisting of:

6. 2. A process according to claim 1, characterized in that the polyol contained in composition (B) has a hydroxyl functionality equal to 2.

7. 2. A process according to claim 1, characterized in that the polyol contained in composition (B) is a polyether diol, preferably a polyoxypropylene diol.

8. The carboxylic acid diol (C) used in step (i) is represented by the formula (iC), ・R 0 represents an alkyl group containing 1 to 4 carbon atoms, preferably a methyl, ethyl or n-propyl group, and even more preferentially a methyl group, x and y are the same and equal to 1, and / or 2. The method of claim 1, wherein z is equal to 0.

9. The tertiary amine (D) used in step (ii) is - polyethyleneimine, - polypropyleneimine, triethylamine, ・Structural formula: 1,8-diazabicyclo[5.4.0]undec-7-ene (or DBU) having the formula ・Structural formula: 1,4-diazabicyclo[2.2.2]octane (or DABCO) having the formula ・Structural formula: 1,5-diazabicyclo[4.3.0]non-5-ene (or DBN) having the formula N,N-dicyclohexylmethylamine (or DCHMA); and Trihexylamine (or THA) 2. The method according to claim 1, characterized in that the compound is selected from the group consisting of:

10. The aminosilane (E) used in step (iii) has the formula (iiiE), ・R 3 represents a methylene or n-propylene group; ・R 4 and R 5 may be the same or different and each represents a methyl or ethyl group; p is equal to 0, and / or ・R 6 is a straight chain alkyl group containing 1 to 4 carbon atoms, or R 7 represents a group of formula (IIc) where R is an alkyl group containing 1 to 3 carbon atoms 2. The method of claim 1, wherein the

11. 2. A process according to claim 1, characterized in that it is carried out in the presence of a plasticizer and / or a solvent other than water, preferably introduced in step (i).

12. A composition of ionic silylated copolyurethane containing two ureido-alkylene-alkoxysilane end groups, said composition being obtainable by the preparation process according to claim 1.

13. At least one composition of ionic silylated copolyurethane having ureido-alkylene-alkoxysilane end groups according to claim 12, and at least one filler 1. A crosslinkable adhesive and / or sealant composition comprising:

14. 14. An article comprising the crosslinkable adhesive and / or sealant composition of claim 13 in a sealed package protected from air.

15. 1. A method for assembling two substrates, comprising: - coating the crosslinkable adhesive and / or sealant composition according to claim 13 at room temperature in the form of a layer having a thickness of between 0.2 and 5 mm onto at least one of the two substrates to be assembled, and then - bringing two substrates into effective contact; A method comprising: